REVITALISASI MADRASAH IBTIDAIYAH: STUDI DESKRIPTIF PADA AL-ITTIHAD DARU INDAH JAMBE TANGERANG - Rouf, Ahmad Akso Abdur; Wahidin, Khaerul; Maulana, Muhammad Azka (Universitas Islam Balitar, 2022)
The ethnographic and religious-based school model is the right step and in accordance with the cultural, customary and religious background of the community. Therefore, the purpose of this study is to describe the concept of Madrasas Ibdidaiyah related to the existence of local schools in the midst of modern schools. This research was conducted at Madrasas Al-Ittihad Daru Indah Jambe-Tangerang. This study uses a qualitative approach with descriptive methods. The results of the study indicate that the Al-Ittihad Islamic educational institution is running well and needs to be maintained and certainly improved, in order to face the era of globalization and science and technology as stated in the Vision of Madrasas Al-Ittihad in the form of the realization of people of faith and piety, intelligent and superior in science and technology achievements. and have the spirit of Pancasila. It can be concluded that facing the challenges of the era of Islamic educational institutions, it is necessary to prepare themselves as well as possible so that they are able to face the dynamic conditions of learning in the 21st century.